2019
DOI: 10.1111/1365-2745.13273
|View full text |Cite
|
Sign up to set email alerts
|

Multiple components of plant diversity loss determine herbivore phylogenetic diversity in a subtropical forest experiment

Abstract: 1. Plant diversity loss can alter higher trophic-level communities via non-random species interactions, which in turn may cascade to affect key ecosystem functions. These non-random linkages might be best captured by patterns of phylogenetic diversity, which take into account co-evolutionary dependencies. However, lack of adequate phylogenetic data of higher trophic levels hampers our mechanistic understanding of biodiversity relationships in species-rich ecosystems.2. We used DNA barcoding to generate data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 97 publications
(146 reference statements)
9
58
0
1
Order By: Relevance
“…This lack of attention to backbone‐constrained tree searching occurs despite its apparent utility in integrating diverse data types and its ability to scale phylogenies and to increase information content in fields such as phylogenetic community ecology and metabarcoding (e.g. Liu et al ., ; Wang et al ., ). Here, I developed constraint methodology further for species‐comprehensive matrices with partial overlap to backbone trees, now with clearer delineation of functions which gives more flexibility in the implementation of constraints, depending on considerations such as scale, approach to constraint application, and software used.…”
Section: Discussionmentioning
confidence: 97%
“…This lack of attention to backbone‐constrained tree searching occurs despite its apparent utility in integrating diverse data types and its ability to scale phylogenies and to increase information content in fields such as phylogenetic community ecology and metabarcoding (e.g. Liu et al ., ; Wang et al ., ). Here, I developed constraint methodology further for species‐comprehensive matrices with partial overlap to backbone trees, now with clearer delineation of functions which gives more flexibility in the implementation of constraints, depending on considerations such as scale, approach to constraint application, and software used.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to functional consequences via biotic niche opportunities, woody plant PD may at evolutionary time‐scales have influenced speciation of associated organisms, at least for herbivores (Ehrlich & Raven, 1964). Past co‐speciation between plants and herbivores can result in a phylogenetic signal in herbivore composition and diversity that is independent of niche overlap and resource availability (Becerra, 2015; Pellissier et al, 2013; Wang et al., 2019). Due to their central roles in food webs, herbivores can affect predators, and thus through trophic cascades other trophic levels that are unlikely to have co‐speciated with plants.…”
Section: Discussionmentioning
confidence: 99%
“…Cadotte et al., 2009). For example, it was recently shown that tree PD but not SR explained the ecosystem function parasitism (Staab et al., 2016) and the response of caterpillar communities to changes in host tree diversity (Wang et al., 2019). Additionally, if niche differences among plants enlarge overall biotic niche amplitudes (Figure 1), PD may also increase associated species abundances by allowing higher densities of individuals via higher resource amount (‘more individuals hypothesis’, Srivastava & Lawton, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, even slight changes in taxonomic measures may cause pronounced changes in the functions of ecological communities (Flynn et al ., 2009). Therefore, incorporating a wider range of metrics, including both taxonomic and functional aspects, would help to develop a more comprehensive understanding of the functional consequences of biodiversity losses (Ebeling et al ., 2018; Wang et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%